2017
DOI: 10.3847/1538-4357/837/1/16
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic Web of Galaxies in the COSMOS Field: Public Catalog and Different Quenching for Centrals and Satellites

Abstract: We use a mass complete (log(  M M )  9.6) sample of galaxies with accurate photometric redshifts in the COSMOS field to construct the density field and the cosmic web to z=1.2. The comic web extraction relies on the density field Hessian matrix and breaks the density field into clusters, filaments, and the field. We provide the density field and cosmic web measures to the community. We show that at z0.8, the median star formation rate (SFR) in the cosmic web gradually declines from the field to clusters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
172
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(181 citation statements)
references
References 179 publications
(295 reference statements)
9
172
0
Order By: Relevance
“…The filament-void pattern is well reproduced in cosmological simulations (Doroshkevich et al 1980;Klypin & Shandarin 1983;Davis et al 1985;Gramann 1993;Sheth & van de Weygaert 2004;Springel et al 2005). In recent years, filaments have been found to occur over the wide span of largescale density levels, residing inside voids and superclusters Sousbie et al 2011;Einasto et al 2012;Alpaslan et al 2014;Cautun et al 2014;Darvish et al 2017;Malavasi et al 2017).…”
Section: Introductionsupporting
confidence: 54%
“…The filament-void pattern is well reproduced in cosmological simulations (Doroshkevich et al 1980;Klypin & Shandarin 1983;Davis et al 1985;Gramann 1993;Sheth & van de Weygaert 2004;Springel et al 2005). In recent years, filaments have been found to occur over the wide span of largescale density levels, residing inside voids and superclusters Sousbie et al 2011;Einasto et al 2012;Alpaslan et al 2014;Cautun et al 2014;Darvish et al 2017;Malavasi et al 2017).…”
Section: Introductionsupporting
confidence: 54%
“…Perhaps, instead, the correlation of increased quenched galaxy fractions with environment density is due to a superposition of other possible quenching mechanisms each of which depend on more local factors Blanton et al 2006;Cucciati et al 2010) than the broader environment properties Porter et al 2008;Fadda et al 2008;Darvish et al 2014Darvish et al , 2017Alpaslan et al 2016;Laigle et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As a first step to address these important issues for understanding galaxy evolution, a more comprehensive sampling of star-forming galaxies at the redshifts of z < ∼ 3 is required that covers a wide range in terms of star formation activity and environment. Recent studies have indeed demonstrated the importance of investigating galaxy properties along the cosmic web (e.g., Darvish et al 2014;Darvish et al 2015;Darvish et al 2016;Darvish et al 2017;Malavasi et al 2017;Laigle et al 2017;Kuutma et al 2017). …”
Section: Introductionmentioning
confidence: 99%